The Influence of the Education Management Information System and Teachers' Social Competence on Parental Satisfaction of Students - Syaifudin Syaifudin (SINTESA, 2023)
This study aims to determine and test empirical data related to the Effect of Educational Information Systems and Teacher Social Competence on Parent Satisfaction of Students separately or simultaneously. In this study, the authors used a quantitative method with a correlational approach to quantitative data obtained from the object of research, namely the parents with a research sample of133 respondents from a total population of 202 parents of students. The data was collected using a questionnaire / questionnaire technique. The type of analysis used is correlation and regression analysis which is described descriptively. The results of this study are First, there is a positive and significant influence between the education management information system and parental satisfaction of 44.9 % and it means that the remaining 55.1% is determined by other factors, which means that every one unit increase in the education management information system score will affect the increase in parental satisfaction scores by 0.567. Second, there is a positive and significant influence between the social competence of teachers and parental satisfaction with a correlation coefficient of 55.8%, which means that everyone unit increase in the social competence score of teachers will affect the increasein parental satisfaction scores by 0.800. Third, there is a positive and significantinfluence between the education management information system and the socialcompetence of teachers together on parental satisfaction with a correlationcoefficient of 0.810 and a coefficient of determination R-square of0.656 which jointly influence parental satisfaction of 65.6% and the remaining34.4% is determined by other factors. The regression coefficient is obtained by Ŷ =11.706 + 0.316X1 + 0.581X2, which means that every one unit increase in the education management information system score and the social competence of teachers together will affect the increase in the Parental Satisfaction score of0.897